The Effect of Binahong Leaf Extract on Reducing Cholesterol and Histopathological Features in the Liver - Trisnawati, Risca; Djuang, Michelle Hendriani; Hutapea, Johnson (Newinera Publisher, 2024)
Being overweight or obese raises your risk of elevated cholesterol, triglycerides, and fatty liver. The liver is crucial to metabolic regulation. Essential to preserve liver health. Maintaining your diet, exercising, and eating antioxidants are all options. Many plants contain antioxidants, like Binahong (Anredera cordifolia). This study examines how Binahong leaf extract reduces cholesterol and improves liver function in high-fat-fed Wistar rats (Rattus norvegicus) and their liver histology. An actual experiment or laboratory experimental study is quantitative. 24 Wistar rats were sampled. Binahong leaf extract was the independent variable, cholesterol levels liver histological features were the dependent variable, and a high-fat diet was the precondition. The test animals were put into four groups: control, groups 2, 3, and 4 with Binahong leaf extract at 30mg/BW, 50mg/BW, and 70mg/BW. SPSS normality, homogeneity, and ANOVA tests. If p > 0.05, research results are generally distributed with 0.200 significance. Significant homogeneity was 0.176 > 0.05. Effective One-Way ANOVA test results (0.000 or <0.05). Post Hoc LSD test analysis yielded important values of 0.000.0001 and 0.024 < 0.05. The phytochemical test found flavonoids, alkaloids, saponins, steroids, and tannins in Binahong leaf extract. Binahong leaf extract at 70 mg/BW reduced cholesterol, body weight, and LDL in hypercholesterolemic male white mice best. The study found that Binahong leaf extract's secondary metabolites—flavonoids, alkaloids, saponins, steroids, and tannins—reduce cholesterol, LDL, and body weight in Wistar strain white rats (Rattus Norvegicus) with hypercholesterolemia.